Developing English for Specific Purposes (ESP) Book as Learning Material for Chemistry Students - Uspayanti, Rezky; Indriyani, Novi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
English for Specific Purposes means learning English based on students’ needs. This research focuses on developmental research that aims to develop English for Specific Purposes book for Chemistry Education Department students of Musamus University and also to know the effectiveness of the book on the student's ability in English. The ADDIE Research and Development (R&D) model was used in this research. This ESP book was developed based on the problem and the need of the students in Chemistry Education at Musamus University. This developmental research consisted of five stages including analysis, design, development, implementation, and evaluation. The first was an analysis which means the researcher found out the need of the students before developing the book. The second was designed that prepared the content of the book. The third is a developmental stage that developed the content of the book which consisted of 12 chapters and doing the validation. The fourth is the implementation of the book in the teaching and learning process. The last was doing a trial of the book to know its effectiveness. The students of chemistry education were given the pre-test and post-test based on the content of the book. The pre-test was given before implementing the book while the post-test was given after implementing the book. The results of the ESP book that has been made indicate the following points: 1) the book based on the student's need, 2.) the content of the book was based on learning objectives and the experts gave good comments on the book content, 3.) The mean score for the pretest was 75.77, while the mean score for the post-test was 80.54. The result of this research can be concluded that English for Chemistry Students book was worthy and could improve the English ability of Chemistry Education Department students at Musamus University. Thus, this book can be a reference in the teaching and learning process.